Evaluación de la capacidad de desplazamiento de un edificio de concreto reforzado con sistema combinado y vigas de acople, mediante un análisis estático no lineal (2020)
To apply the knowledge acquired during the postgraduate academic process, and following the NSR-10 regulation, the structural design of a 10-story building is made, this is located in Palmira Valle del Cauca (Colombia), this has a structural system of frames and walls with coupling beams. In addition, the building is subjected to a nonlinear static procedure, using the Etabs Software and the ASCE-41-17 manual, with which the displacement capacity of the building is determined, and as a result of the analysis improvements in the design are considered.